2015
DOI: 10.1097/rlu.0000000000000453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of FDG PET/CT Imaging for Venous Thromboembolic Disorders

Abstract: Although further studies are warranted for further clarification, our preliminary data substantiate that FDG PET/CT is a viable modality for assessing VTE, at least for DVT. We believe our results add positively to the limited data on this subject and are promising enough to warrant further larger series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…[10] In addition, venous thrombosis uptake subsides in the chronic phase to normal values at approximately 3 months, allowing for proper distinction from malignancy in the absence of targeted treatment. [1234] As opposed to previously reported extensive portal vein tumor thromboses,[6] the current case illustrates the interesting pattern of branching metabolic activity in an extensive portal vein thrombosis with mild intrahepatic intensity suggestive of bland thrombosis, highlighting once more the instrumental role of FDG-PET in thrombosis and cancer staging. Unfortunately, in this case, cancer stage was not suitable for curative intent, and the patient received appropriate palliative therapy.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…[10] In addition, venous thrombosis uptake subsides in the chronic phase to normal values at approximately 3 months, allowing for proper distinction from malignancy in the absence of targeted treatment. [1234] As opposed to previously reported extensive portal vein tumor thromboses,[6] the current case illustrates the interesting pattern of branching metabolic activity in an extensive portal vein thrombosis with mild intrahepatic intensity suggestive of bland thrombosis, highlighting once more the instrumental role of FDG-PET in thrombosis and cancer staging. Unfortunately, in this case, cancer stage was not suitable for curative intent, and the patient received appropriate palliative therapy.…”
mentioning
confidence: 49%
“…Due to neutrophils and macrophages activated by the acute inflammatory phase of venous thrombosis, FDG-PET sports high sensitivity and specificity. [1234] Various cancers are associated with bland or tumor thrombosis, including hepatocellular carcinoma, pancreaticobiliary carcinoma, renal cell carcinoma, and various adenocarcinomas. [56789] As proposed by recent literature, FDG-PET may differentiate direct tumor invasion from bland thrombus.…”
mentioning
confidence: 99%
“…By visual interpretation, DVT/PE was considered present if focal or linearly increased FDG uptake was observed within the veins/pulmonary vasculature. FDG-PET/CT was able to correctly diagnose or rule out DVT in all patients, but was positive in only two of six PE cases [14]. Based on the same data and reported in an abstract [64], the same researchers found that the volumetric parameters metabolically active volume (MAV), total lesion glycolysis (TLG), and SUVmax relative ratios were the most robust predictors of DVT, while areas under the ROC curve were 0.96 for MAV (p=0.005), 0.94 for TLG (p=0.007), and 0.89 for SUVmax (p=0.03).…”
Section: Discussionmentioning
confidence: 86%
“…without PETimaging. Of the included papers, five papers were on the diagnostic performance of PET/CT in DVT (n=3) or PE (n=3) [11][12][13][14][15], and four were on the ability of PET/CT to differentiate TT from BT [16][17][18][19]. Two papers presented data on changes in FDG uptake over time [12,20].…”
Section: Resultsmentioning
confidence: 99%
“…With reference to related mechanisms and experience, PET may have a greater role in the detection of venous thromboembolism compared with the detection of pulmonary embolism [ 80 , 81 ]. A prospective study evaluated the significance of 18 F-FDG PET in the detection of lower extremity venous thrombosis and pulmonary embolism [ 82 ]. The results showed that physicians diagnosed all 7 patients with lower extremity venous thrombosis based on the hypermetabolism of thrombus and blood vessels, but only 2 of 6 patients with pulmonary embolism were accurately diagnosed [ 82 ].…”
Section: Potential Role Of Pet In Covid-19-derived Complicationsmentioning
confidence: 99%